Australian football players' Achilles tendons respond to game loads within 2 days: an ultrasound tissue characterisation (UTC) study. Issue 3 (15th April 2014) - Rosengarten, Samuel D; Cook, Jill L; Bryant, Adam L; Cordy, Justin T; Daffy, John; Docking, Sean I
Abstract : Background/aim: The Achilles tendon is a tissue that responds to mechanical loads at a molecular and cellular level. In vitro and in vivo studies have shown that the expression of anabolic and/or catabolic proteins can change within hours of loading and return to baseline levels within 72 h. These biochemical changes have not been correlated with changes in whole tendon structure on imaging. We examined the nature and temporal sequence of changes in Achilles tendon structure in response to competitive game loads in elite Australian football players. Methods: Elite male Australian football players with no history of Achilles tendinopathy were recruited. Achilles tendon structure was quantified using ultrasound tissue characterisation (UTC) imaging, a valid and reliable measure of intratendinous structure, the day prior to the match (day 0), and then reimaged on days 1, 2 and 4 postgame. Results: Of the 18 participants eligible for this study, 12 had no history of tendinopathy (NORM) and 6 had a history of patellar or hamstring tendinopathy (TEN). Differences in baseline UTC echopattern were observed between the NORM and TEN groups, with the Achilles of the TEN group exhibiting altered UTC echopattern, consistent with a slightly disorganised tendon structure. In the NORM group, a significant reduction in echo-type I (normal tendon structure) was seen on day 2 (p=0.012) that returned to baseline on day 4. Summary: There was a transient change in UTC echopattern in the Achilles tendon as a result of an Australian football game in individuals without a history of lower limb tendinopathy.